2014
DOI: 10.1155/2014/760694
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oxidative Stress Enzymes and Structural and Functional Proteins on Human Aortic Tissue from Different Aortopathies

Abstract: The role of oxidative stress in different aortopathies is evaluated. Thirty-two tissue samples from 18 men and 14 women were divided into: 4 control (C) subjects, 11 patients with systemic arterial hypertension (SAH), 4 with variants of Marfan's syndrome (MV), 9 with Marfan's syndrome (M), 2 with Turner's syndrome, and 2 with Takayasu's arteritis (TA). Aorta fragments were homogenized. Lipoperoxidation (LPO), copper-zinc and manganese superoxide dismutase (Mn and Cu-Zn-SOD), catalase (CAT), glutathione peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 88 publications
3
63
0
1
Order By: Relevance
“…Needless to say, it remains possible that apocynin has other beneficial off‐target affects, including acting as a ROS‐scavenger, blocking other elastases or increasing SMC proliferation . Several investigators have studied the involvement of ROS in thoracic aortic root/ascending aortic aneurysm formation, including individuals with MFS, as well as patients with bicuspid aortic valves . The hypothesized important role of ROS in MFS aneurysm formation presented here agrees with the findings of Jimenez‐Altayo et al who also reported increased nitrotyrosine residues in both aortic aneurysms and cultured SMC from MFS patients .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Needless to say, it remains possible that apocynin has other beneficial off‐target affects, including acting as a ROS‐scavenger, blocking other elastases or increasing SMC proliferation . Several investigators have studied the involvement of ROS in thoracic aortic root/ascending aortic aneurysm formation, including individuals with MFS, as well as patients with bicuspid aortic valves . The hypothesized important role of ROS in MFS aneurysm formation presented here agrees with the findings of Jimenez‐Altayo et al who also reported increased nitrotyrosine residues in both aortic aneurysms and cultured SMC from MFS patients .…”
Section: Discussionsupporting
confidence: 87%
“…C, In vitro quantification of NADPH oxidase activity by LGCL in Fbn1 AS and Des SMCs treated with AngII or vehicle (n = 6, *P = .03). D, In vitro quantification of NADPH oxidase activity by LGCL in Fbn1 AS SMCs treated with AngII and with either TGF-β neutralizing antibody (TGFb NA) or vehicle (n = 6, *P = .009) ascending aortic aneurysm formation, including individuals with MFS, 24,27,[40][41][42] as well as patients with bicuspid aortic valves. [43][44][45] The hypothesized important role of ROS in MFS aneurysm formation presented here agrees with the findings of Jimenez-Altayo et al who also reported increased nitrotyrosine residues in both aortic aneurysms and cultured SMC from MFS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies in animal models of MFS have shown that the expressions of the precursor enzymes of O 2 − , xanthine oxidase, and NADPH oxidase are increased [ 8 ]. A previous study from our laboratory has shown an increase in oxidative stress and an alteration of the antioxidant enzymes super oxide dismutase (SOD) and glutathione peroxidase (GPx) in the aortic aneurysm of MFS patients [ 9 ]. In addition, antioxidants enzymes such as glutathione peroxidase (GPx) and glutathione-S-transferase (GST) require GSH as cofactor for ROS detoxification [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction and downregulated NO would contribute to the stiffness, reduced distensibility, and aortic complications such as AOD [ 5 ] . Our results showed a decrease of nitrite levels in SAS group may be due to endothelium dysfunction.…”
Section: Discussionmentioning
confidence: 99%